Analysis of the Effect of Human Development Index, Poverty, and Islamic Philanthropy on Economic Growth: An Empirical Study in Aceh Province - Muhammad Yusuf Harahap; Yusrizal Yusrizal; Nurma Sari; Mira Chairani; Zulfa Khairina Batubara; Susi Herawati (Brilliant International Journal Of Management And Tourism, 2025)
Inclusive economic growth is a key priority in regional development, particularly in areas that adopt an Islamic economic system, such as the City of Banda Aceh. However, challenges such as persistent poverty and the suboptimal utilisation of Islamic philanthropy continue to hinder the strengthening of regional economic performance. This study aims to examine the effects of the Human Development Index (HDI), poverty rate, and zakat/infaq/sedekah (ZIS) on the economic growth of Banda Aceh from 2015 to 2024. A quantitative approach was employed, using a time series linear regression model. Secondary data were obtained from the Central Bureau of Statistics (BPS), Baitul Mal Aceh, and other official sources. The findings reveal that HDI has a positive and statistically significant effect on economic growth. In contrast, poverty and ZIS do not have a significant individual impact. Nevertheless, the model demonstrates strong explanatory power, with a significance level of 0.002. These results suggest that improving human capital through HDI is a critical driver of economic growth. Accordingly, development policies in Banda Aceh should prioritise investment in education and health sectors, alongside the expansion of productive zakat programmes, to foster sustainable economic growth rooted in Islamic values.